2015
DOI: 10.1128/mcb.00300-15
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Inflammatory Signaling upon Charcot-Marie-Tooth Type 1C Mutation of SIMPLE Protein

Abstract: Endosomal trafficking is a key mechanism to modulate signal propagation and cross talk. Ubiquitin adaptors, along with endosomal sorting complex required for transport (ESCRT) complexes, are also integrated to terminate ligand-receptor activation in late endosomes and multivesicular bodies (MVBs). Within these pathways, we recently demonstrated that the protein SIMPLE is a novel player in MVB regulation. SIMPLE is also clinically important and its mutation accounts for the Charcot-Marie-Tooth type 1C (CMT1C) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 108 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, cycloheximide chase experiments in vivo suggested that the V144M construct was degraded more rapidly compared to wild type. It is therefore tempting to speculate that all CMT1C mutations might lead to similar structural alterations within the LITAF domain, resulting in an unstable and toxic interaction with lipid head groups and consequent endocytic membrane disruption [10, 56]. This aberrant association of LITAF with membranes might lead to the dysfunctional trafficking of Schwann cell membrane receptors, including growth factor receptors [9, 57, 58] and cell adhesion molecules [6, 59], with consequent disruption of the critical endocytic pathways that maintain the integrity of peripheral nerve myelin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cycloheximide chase experiments in vivo suggested that the V144M construct was degraded more rapidly compared to wild type. It is therefore tempting to speculate that all CMT1C mutations might lead to similar structural alterations within the LITAF domain, resulting in an unstable and toxic interaction with lipid head groups and consequent endocytic membrane disruption [10, 56]. This aberrant association of LITAF with membranes might lead to the dysfunctional trafficking of Schwann cell membrane receptors, including growth factor receptors [9, 57, 58] and cell adhesion molecules [6, 59], with consequent disruption of the critical endocytic pathways that maintain the integrity of peripheral nerve myelin.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that GDAP1 acts as a sensor of the reduced to oxidized glutathione ratio (GSH/GSSG) participating in the release of an antioxidative response causing the recovery of GSH/GSSG. These results suggest a possible role of oxidative stress and chronic inflammation in the pathogenesis of GDAP1-related CMT, as shown to occur in other forms of CMT such as CMT1A [30] or CMT1C [31].…”
Section: Proposed Roles Of Ganglioside-induced Differentiation-assmentioning
confidence: 66%
“…Axonal degeneration and increased disability occur over time. Among other molecular mechanisms of demyelination in CMT1, oxidative stress, inflammation, autophagy impairment, and mitochondrial dysfunction, have been proposed [ 7 , 8 , 9 , 13 , 14 , 15 , 16 , 42 , 43 ]. Moreover, skeletal muscle atrophy induced by denervation is associated with excessive mitochondrial ROS formation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in rats and mice demonstrate an association of peripheral neuropathy with a reduction of the antioxidant status with low levels of GSH, and of glutathione peroxidase (GPx) and reductase (GRd) activities, and an increased lipid peroxidation [ 15 ]. The excess of ROS induces the activation of NF-κB and NF-κB-dependent pro-inflammatory cytokines including IL-1b in CMT patients [ 16 ]. Evidences for macrophage-dependent inflammatory activation and myelin disruption has been shown in a murine model of CMT1A [ 17 ].…”
Section: Introductionmentioning
confidence: 99%